Função Pulmonar de pacientes submetidos a Cirurgia Bariátrica - Ambrozin, Alexandre Ricardo Pepe [UNESP]; Manzano, Roberta Munhoz [UNESP]; Santos, André Luiz dos; Quitério, Robison José [UNESP] (My University, 2014)
Introduction: Obesity is a risk factor for postoperative pulmonary complications. Overweight can alter respiratory mechanics and decrease lung volumes and capacities. Bariatric surgery (BS) has been used as treatment for morbid obesity, but this surgery can lead to respiratory complications. Objective: To evaluate pulmonary function in morbid obese patients undergoing bariatric surgery. Methods: The patients were submitted to pulmonary function testing, including slow and forced vital capacity (SVC and FVC), forced expiratory volume in the first second (FEV1), Tiffenau index (FEV1/FVC), forced expiratory flow 25-75% (FEF25-75%) and maximal inspiratory and expiratory pressure (MIP and MEP). Descriptive analysis was performed. Results: We evaluated 18 patients, mean age of 37.33 ± 11.23 years, height 1.65 ± 0.09 m, weight 125.92 ± 25.24 kg and BMI 46.34 ± 9 20 kg/m2 , SVC 100.64 ± 22.91%, FVC 102.04 ± 21.82%, FEV1 104.85 ± 22.16%, FEV1 /FVC 83.54 ± 6.63% and FEF25-75% 84.47 ± 25.74%, 99.75 ± 24.55 for MIP and MEP 102.12 ± 25.06 cmH2O. Conclusion: The bariatric surgery candidates had normal values for manovacuometry and spirometry.

Introdução: A obesidade é considerada um fator de risco para complicações pulmonares pós-operatórias. A cirurgia bariátrica tem sido utilizada como recurso terapêutico no tratamento da obesidade mórbida. Objetivo: Avaliar a função pulmonar de pacientes obesos mórbidos candidatos à cirurgia bariátrica. Métodos: Os pacientes foram submetidos à prova de função pulmonar, por meio da espirometria e manovacuometria, e foram avaliados a capacidade vital lenta e forçada (CVL e CVF), volume expirado forçado, no primeiro segundo (VEF1 ), relação VEF1 /CVF, fluxo expiratório forçado 25-75% (FEF25-75%) e pressão inspiratória e expiratória máxima (Pimáx e Pemáx). Resultados: 18 pacientes (4 homens e 14 mulheres), com idade média 37,33±11,23 anos, altura 1,65±0,09 metros, peso 125,92±25,24 kg e IMC de 46,34±9,20 kg/m2 , CVL 100,64±22,91%, CVF 102,04±21,82%, VEF1 104,85±22,16%, VEF1 /CVF 83,54±6,63% e FEF25-75% 84,47±25,74%, Pimáx de 99,75±24,55 cmH2 O e Pemáx 102,12±25,06 cmH2 O. Conclusões: Os pacientes candidatos à cirurgia bariátrica apresentaram espirometria e manovacuometria dentro da normalidade.
Keywords: obesidade; Espirometria; Cirurgia Bariátrica; função pulmonar